Managing the Operation of Call Center: An Attempt to Improve Service Quality for Costumer Satisfaction Case Study: PT. Astra International, Tbk - AstraWorld - Mukhaiyar, Hadi; Firman, Aries F. (The Indonesian Journal of Business Administration, 2013)
As CRM company for automotive industry, AstraWorld face so many challenges, especially in call center services. Almost every day, our end customers make interaction with call center agents 24 hours and 7 days. The activities are also different and depend on the customers needs, such as inqueries, booking, complaint, customer requests, emergency assistance, etc. But during that time, there is none survey to measure whether the customer feel satisfied or dissatisfied so the company able to set a strategic to improve the operational quality of service. Another fact found from our database analysis research that the customers will make interaction with the call center after 6 month â€“ 12 month later. So looking at this condition, positive or negative services given will determine the customers level of satisfaction or event determine whether the customer want to use call center services again. This project will share about what is the real expectation that the customers bring while using call center and how to manage the operational call center with excellent services. Initial survey from all aspects that affect Customer Satisfaction (CSAT) Index is conducted to all customers who ever made interaction with call center, such as System Accessibility, Process & Procedures, and People. System accessibility related how easy the customers able to reach call center agent after dialing up the hotline number. Process & procedures related on how flexible information requested able to deliver to the customers. And people related to agents level of competencies and knowledge in delivering all customers needs. To be able to find the root cause then additional surveys are required both from internal agents perspective and customers perspective. The problem solution offered focus on quality internal improvement, include Developing People Competencies and Enhancing Knowledge Management Features. Through these strategies hopefully able to develop professional call center agents with excellent services standards. And of course able to improve company CSAT score. Â Keywords: Call Center, Customers, Service Quality, Call Center Agent, Customer SatisfactionÂ